Severe metabolic accumulation of VV116 in kidney transplant patients with impaired renal function: a case series report - Zhang, Jiaying; Gao, Yuan; Miao, Xiaoyun; Wang, Wei; Zhou, Zhongkai; Gao, Yunyi; Liu, Liwei; Wu, Menghua; Ma, Ke; Zhou, Ling; Yang, Yan; Meng, Sha; et al. (Frontiers in Immunology, 2025)
The treatment of COVID-19 in the post-transplant individuals is challenging, primarily due to the drug-drug interaction between nirmatrelvir/ritonavir and tacrolimus. Deuremidevir hydrobromide tablets (VV116) is an orally small molecule agents target SARS-CoV-2 RdRp and inhibits viral replication. It may have a low likelihood of drug-drug interactions and has a potential to provide new treatment option. We described three cases of renal transplant patients with concomitant impaired renal function who developed COVID-19 pneumonia and were treated with VV116. Despite varying degrees of drug accumulation, these patients achieved rapid viral clearance and showed prompt improvement in pneumonia symptoms. Notably, tacrolimus blood concentrations remained within the therapeutic range throughout treatment, and no clinically significant adverse events were observed despite the drug accumulation.